Transdisciplinarity and dialogismo as foundations of the teaching action: a proposal for a reading class - Souza, André Felipe Pereira de (Revista Letras Raras, 2023)
Even in the face of innovations arising from contemporary times, there is still much to move forward to achieve education based on universality, socioideological debate, pluralism of ideas and the complexity of human thought. This time, the present work aims to reflect how the theoretical contributions presented here can subsidize the pedagogical work of the teacher, when conceiving language as a process of social interaction, as advocated by the Bakhtin Circle. Therefore, a bibliographical review of the discussions of Nicolescu (2000) is made, which discusses the principle of transdisciplinarity, the reflections of Morin (2010), as the theory of complexity and knowledge necessary for the education of the future, in addition to the questions related to the dialogic theory of language proposed by the Bakhtin Circle (1988 [1975]; Volóchinov, 2013 [1930]; Medviédev, 2019 [1928]), correlating these theories to the teaching action in basic education. In summary, it is believed that the discussions brought in this article may help the Portuguese language teacher to face the challenges imposed by education of the XXI century, and contribute to the expansion of the socioideological consciousness of teachers.